Sharing Pengalaman Belajar di Luar Negeri dan Pengenalan TOEFL Bagi Penghuni Asrama Mahasiswa Katolik Tauboria di Jayapura - Servo Kocu; Adelce Ferdinandus; Rommy Rambet; Amelina Sobolim (LPPM Uncen, 2026)
English language proficiency is one of the competencies that is currently in high demand in academic and professional fields around the world. TOEFL is often used as an indicator to measure a person's ability as a requirement for further study or international scholarships. However, not many students, especially in Papua, have the opportunity to improve their English skills, particularly in taking the TOEFL exam. One of the reasons for this is that the cost of TOEFL tests and training is relatively high, while almost all scholarships currently available in Indonesia require proof of English proficiency, such as TOEFL or IELTS. This community service activity aims to increase students' motivation to continue their studies abroad by sharing experiences of studying abroad and introducing TOEFL testing. The activity was held at Tauboria Dormitory, Jayapura, involving students from several universities in Jayapura who reside at Tauboria Dormitory. The method used was training-based counseling, which included sessions on sharing overseas study experiences, scholarship information, introduction to the TOEFL ITP structure, and TOEFL practice tests. Initial survey results showed that 100% of participants had never taken the TOEFL test, even though 80% had studied English for more than six years in formal education. The practice test results showed an average score of 383, indicating initial familiarity with the test format. The evaluation of the activity showed that participants considered it useful in increasing their motivation for further study and understanding of the TOEFL, although their confidence in taking the test still needed to be improved through more continuous training. This activity shows that integrating motivation for further study and TOEFL training can be an effective strategy in raising student awareness of the importance of English in relation to employment and further study opportunities.